Comparison of conventional and standardized bone densitometry around implants in periapical radiographs during a three months period - Asieh Zamani Naser; Shahab Etemadi; Mansour Rismanchian; Mahnaz Sheikhi; Mohammadbagher Tavakoli (Wolters Kluwer Medknow Publications, 2011)
Background: Comparing continuous films taken at different timescales is a way to study the alveolar bone changes around the implant over time. One of the important concerns in quantitative analysis of the alveolar bone changes over the time is to reduce variations in the X-ray imaging geometry and image density. Methods : Using a modified XCP film holder together with the bite recording material, parallel periapical radiographs were taken from the implants placements of 16 patients in four steps. Densities of radiographs were measured in a conventional way using the video densitometry device. The same films were also scanned; sequential radiographic density of each patient was homogenised and the density was measured. Density changes obtained in both methods were compared. The data were evaluated using ANOVA, paired t-test and Pearson correlation (α = 0.05). Results: In the conventional method of densitometry, the average densities were as follows: before operation 1.0044, after one week 0.9600, after one month 0.9469 and after three months 0.9398. Also, in the standard method of densitometry, the average densities were as follows: before operation 111.7013, after one week 113.4225, after one month 119.4075 and after three months 131.1162. Average density in conventional densitometry were not significantly different in various time stages (P = 0.395). But, the standard densitometry method showed a significant difference (P = 0.001). Conclusion: The average density obtained at different stages in the standard densitometry showed a gradual increase in the bone density in the entire process. Standardising the patient's consecutive radiographic images is essential for quantitative measurements over the time.